Pengaruh Kemudahan Penggunaan Aplikasi Shopee Terhadap Minat Beli Ulang: Perspektif Mahasiswa - Sadiki, Turfa Najmi; Ivo Agesti Dwiyanti (International Journal Administration, Business & Organization, 2021)
At the time of Covid-19 pandemic, e-commerce was the best choice for consumers to purchase their needs. E-commerce most frequented in Indonesia was Shopee. This study aims to determine the effect of the ease of use of the shopee application on the repurchase interest of shopee e-commerce consumers during the Covid-19 pandemic (a case study of Bandung State Polytechnic students). This research is a quantitative study using associative methods. The sampling method in this study is the method nonprobability sampling with snowball sampling technique. In this study, the sample size was 138 respondents. Data processing use software SPSS (statistical program for social science) for windows. The test results show that the ease of using the Shopee application has an effect on consumer repurchase interest.